The relationship in between self-esteem levels and the mothers' expressed emotion in children with asthma - KARADAĞ, BÜLENT TANER; PERDAHLI FİŞ, NEŞE (TURKISH PEDIATRICS ASSOC, 2011)
Aim: The objective of this study is to evaluate the self-esteem levels of asthmatic children and the maternal emotional expressiveness. Material and Method: Sixty-five children and adolescents with the diagnosis of asthma were compared with a control group of 76 children, without a chronic illness. Presence of psychopathology was evaluated by Kiddie-Schizofrenia Affective Disorders Schedule, behavioral problems were assessed by Child Behaviour Checklist. Additionally, Piers Harris Self-Esteem Inventory and Expressed Emotions Questionnaire were administered to children and adolescents and to their mothers, respectively. In order to compare the groups, chi square and student's t-tests, and to assess the relationship between the variables Pearson's correlation analyses were used. Results: Psychiatric diagnoses (p=0.00) and behavioral problems (p<0.01) were encountered more frequently in children with asthma. Although self-esteem levels of asthmatic children were similar to those of the control group, as maternal emotional expression increased, children tended to have lower self esteem levels (r=-0.38, p=0.002). Maternal emotional expression levels were found to be higher in the asthma group (p=0.006) and it showed positive correlation with the presence of psychopathology and behavioral problems in the children. Conclusions: Although self-esteem was not directly affected by the presence of asthma, co-occurrence of psychiatric disorders, emotional and behavioral problems, and high maternal emotional expressiveness result in decreased self-esteem in children. (Turk Arch Ped 2010; 45: 144-9)
Keywords: Asthma; child; expressed emotion; self-concept; MATERNAL DEPRESSIVE SYMPTOMS; INNER-CITY CHILDREN; ADOLESCENTS; ADJUSTMENT; SEVERITY; STRESS